Albuminuria, structural brain findings and Circulating biomarkers of brain injury in older adults - Jens W. Horn; Alison Fohner; Russell Tracy; Hieab H. H. Adams; Luc Djousse; Solfrid Romundstad; Imre Janszky; W. T. Longstreth; Kenneth J. Mukamal (Scientific Reports)
Abstract Albuminuria reflects systemic endothelial dysfunction, but its relationships with subclinical brain abnormalities have not been comprehensively catalogued. The Cardiovascular Health Study recruited older adults from four US communities, beginning in 1989–1990. Systematic measurements of albuminuria were performed in 1996–1997; two brain MRIs, in 1992–1994 and 1997–1999; and serum neurofilament light chain (NfL) measurements from 1996–1997 stored samples. We examined the associations of albuminuria with longitudinal progression of white matter hyperintensities (WMH) and ventricular size, incident infarcts, and cross-sectional quantitative brain volumes and circulating biomarkers of neuronal injury (n = 834–1950). Albuminuria was positively associated with ventricular grade worsening (odds ratio per doubling 1.10, 95% confidence interval (CI) 1.01–1.19) and with circulating NfL levels (2% higher per doubling, 95% CI 1–4%), even after adjustment for vascular risk factors. Albuminuria was also associated with worsening of WMH, incident infarcts, and quantitative WMH and hippocampal volumes, but these latter associations appeared to reflect burden of cardiovascular risk factors. Albuminuria is independently associated with worsening ventricular size and circulating NfL, suggesting a specific role of microvascular dysfunction in brain atrophy. It also reflects cardiovascular risk factor burden on markers of vascular brain injury. These results highlight the diverse associations of albuminuria with common brain abnormalities of aging.